IMPLEMENTING FINANCIAL STATEMENT SYSTEM AT TOKO SINAR INDAH JAYA - Jesclin Jesclin; Wisnu Yuwono (ConCEPt - Conference on Community Engagement Project, 2022)
This community service program aims to design and implement a financial statement recording system at Toko Sinar Indah Jaya. Toko Sinar Indah Jaya's obstacle is using a manual and inefficient financial recording that consumes time and high risk of posting errors. The methods used in this project include interviews, observation, design and implementation. This community service program is carried out during September 2021 – December 2021. Implementing the financial reporting system has helped business strategies within financial control, and it is easy to obtain updated financial reports anytime. The recommendation for a further project is to develop a system for recording financial statements using a computerized system to produce more diverse and demanded financial reports